Prevalence of Fluorosis in Endemic Area of Sonebhadra, Uttar Pradesh: A Pilot Epidemiological Survey - Vinay Kumar Gupta; Gaurav Mishra; Atrey J. Pai Khot; Seema Malhotra; Nishita Kankane (Wolters Kluwer Medknow Publications, 2024)
Background A long-term excess of fluoride ingestion from drinking water, food substances, and industrial pollution may result in fluorosis, a public health hazard. This survey aims to investigate the prevalence of dental and skeletal fluorosis, as well as the role of dietary variables. Materials and Methods A cross-sectional survey was conducted in Sonebhadra district. The Dean's Fluorosis Index and physical exercises demonstrated by the United Nations International Children's Emergency Fund for diagnosing dental and skeletal fluorosis, respectively. The dietary habits of the participants were ascertained using a prevalidated questionnaire. Results The participants' socioeconomic status varied widely with heterogeneity. The frequent abnormalities found were genu varum (21.5%), genu valgum (6.8%), dental fluorosis (52.3%), and skeletal fluorosis (25.8%). Consequently, eight cases reported of multiple deformities. Conclusion The findings showed the increased prevalence of moderate-to-severe fluorosis in fluoride endemic areas of Sonebhadra district. Dental fluorosis was more common in those aged 18-64 years, particularly in males, but skeletal fluorosis increased with age.